IMPLEMENTATION LEARNING OF AKIDAH AKHLAK THROUGH THE BURHANI APPROACH - Maratul Qiftiyah (AT-TAJDID, 2022)
The research aims to describe the implementation of moral learning through the burhani approach at MI NU Sumber Agung. This research uses qualitative methods with a descriptive approach. The instruments used in this research include interviews and observations. From the results of this research can be realized that the implementation of moral learning through the burhani approach in MI NU Sumber Agung on the material obedient and obedient to parents sub material: first, obey the advice of parents by implementing small things like maintaining the cleanliness of the classroom environment. Second, to care for parents by carrying out small things like always being dear to the teacher as a substitute for both parents in the house and dear to his friends. Thirdly, manners and courtesy by carrying out small things like mutual respect to their teachers or fellow friends. Fourth, being honest by carrying out small things such as when the teacher gives a question to be done by the students, the teacher gives emphasis to the students, to be honest like not cheating his friend.